UNDANG UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA DAN PERLINDUNGAN HUKUM BAGI PENCIPTA KARYA CIPTA MUSIK DAN LAGU - Hulman Panjaitan (to-ra, 2019)
Abstract The meaning of song and music is different, but copyright literature does not seem to distinguish them. In the library of international law, the term commonly used to refer to a song or music is musical work. The Bern Convention states that one of the protected works is music compositions with or without words. There is no explicit description in the Bern Convention about what musical work really is. However, from the existing provisions it can be concluded that there are two types of music creation that are protected by copyright, namely music with words and music without words. Music with meaningful words is a song whose elements consist of melody, arrangement lyrics, and notation, while music without words is music that only consists of elements of melody, arrangement and notation. Keywords: copyright literature; the Bern Convention; protected works.